Técnicas agroecológicas no desempenho agronômico e qualidade dos frutos da pimenta biquinho - Labigalini, Isabella (2019)
Alternative practices in food production, which take into account the ecological sustainability of agroecosystems and the economic sustainability of farmers, are being increasingly tried and recommended. The objective of this work was to study the effects of green manure, Trichoderma asperellum and homeopathy on the agronomic performance and fruit quality of the “biquinho” pepper (Capsicum chinense Jacq.). The design was in a randomized complete block with four replications, in subdivided plots, the plot being two homeopathic preparations: 1) Arnica montana 6CH; 2) Pulsatilla nigricans 6CH; and control treatment, and the subplot 7 treatments: 1) Crotalaria juncea sown 50 days before the transplanting of the pepper plants, in the density 25 kg ha-1, managed at 50 days after sowing and regrowth at 91 days; 2) Crotalaria juncea sown 50 days before the transplanting of the peppers, in the density 50 kg ha-1 handled at 50 days after sowing and regrowth at 91 days; 3) Crotalaria juncea sown concomitant to pepper transplant in density 50 kg ha-1, handled at 59 days; 4) Canavalia ensiformis, seeded concomitant with peppermint transplant, density 25 kg ha-1, handled at 48 days; 5) Cajanus cajan, seeded concomitant with pepper transplant, density 25 kg ha-1, handled at 76 days; 6) Trichoderma asperellum inoculated in two moments; and 7) Control 2 (single crop). It was evaluated the height, stem diameter, relative chlorophyll index and normalized difference vegetation index (NDVI) of the pepper plants, production components fruit quality, and sensory analysis. There was interaction between homeopathic preparations and green manures/T. asperellum, which influenced the characteristics of the pepper plants, and there was also interaction between the for all variables analyzed (height, diameter, NDVI, IRC). Biometric values and fruit quality components were only influenced by green manures/T . asperellum, except the number of locules that altered according to the homeopathic preparation used. In sensory analysis there was significant difference only for fruit size, but this did not influence preference. The homeopathic preparations Arnica montana and Pulsatilla nigricans 6CH influenced the biometric characteristics of the pepper plants: height, stem diameter, normalized difference vegetation index (NDVI) and relative chlorophyll index (IRC). T. asperellum exerted influence showing some of the best results on the biometric characteristics of the pepper plants, and when associated with the application of the homeopathic preparation Arnica montana 6CH provided higher heights of plants and IRC. As for production, this did not differ from control. It was concluded that the 50 kg ha-1 intercropping with Crotalaria juncea seedlings sown 50 days before the transplanting of the pepper allowed a good development of the baguier pepper, with production similar to the control, fruits with better pH values, soluble solids, acidity and maturation index.